Peculiarities of the Substantive Defence of the Debtor Against Enforcement in Polish and Lithuanian Law - Derlatka, Joanna; Tamošiūnienė, Egidija (Teisė, 2026)
Studies of enforcement proceedings are usually limited to analysing the effectiveness or specific features of the application of procedural rules governing compulsory enforcement proceedings. This focus of scientific research on the area regulated by procedural law is based on the classic distinction between investigative and enforcement proceedings, recognising that all disputed facts have already been established in civil proceedings (investigative proceedings), while the enforcement proceedings seek only to enforce the court decision as quickly as possible. However, this article aims to reveal how substantive law measures can influence enforcement proceedings that have already been initiated. The object of the study is to analyse the remedies available to the debtor under substantive law against the enforcement proceedings that have already begun, to distinguish them from procedural remedies in the enforcement proceedings, and to reveal their exceptional nature. The article provides a comparative analysis of these measures in Polish and Lithuanian civil proceedings, by revealing their similarities and differences and comparing how the same objectives are pursued by different means. In Poland, the debtor’s right to challenge the basis of the enforcement process is clearly established in civil procedure law, while, in Lithuania, this right of the debtor is recognised in court practice, with its exceptional nature being emphasized. The conclusions at the end of the article emphasize that the debtor may use such measures in exceptional cases and for a limited period, while also seeking to balance the interests of the creditor (recovery agent) in the enforcement process.
Keywords: investigation proceeding; enforcement proceeding; judicial control over the enforcement proceedings; debtor’s defence measures